Efektivitas Partisipasi Masyarakat Dalam Pelaksanaan Pilkada Kota Sukabumi Tahun 2013 Dan 2018 - Muhammad Ghiffar Al Ikhsani; Dine Meigawati; M. Rijal Amirulloh (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effectiveness of community participation in the implementation of the Regional Head Elections (Pilkada) in Sukabumi City in 2013 and 2018. Using a qualitative descriptive approach, this study examines three indicators of effectiveness according to Duncan in Steers (1985), namely goal achievement, integration, and adaptation. Data were obtained through in-depth interviews with the Chairman of the Sukabumi City KPU, field observations, and document analysis. The results showed that community participation in the 2013 Pilkada reached 69% and increased to 72% in the 2018 Pilkada. Despite a strong legal foundation and diverse socialization efforts, the Pilkada has not been running effectively due to participation rates that are still far from ideal. Low participation is caused by multidimensional factors, including public trust crises, voter data administration problems, socioeconomic constraints, and uneven information distribution.